The relationship between nurses’ performance during endotracheal suctioning with their emotional intelligence in Neonatal Intensive Care Units (NICU) - Rahimi Roozbahani, Azadeh; Daneshvar Ameri, Zahra; Hassanpour, Marzyeh; Ranjbar, Hadi (Advances in Nursing & Midwifery, 2017)
Abstract: Background and Aim: Individual skills and psychological characteristics of nurses may affect their efficiency and working quality. In this study, the relationship between emotional intelligence and nurses’ performance during endotracheal suctioning in neonatal intensive care units was assessed. Materials and methods: This was a correlation-descriptive study which was conducted on 67 nurses working in neonatal intensive care units of Tehran Medical Sciences university hospitals in 2016. The data was collected with a check-list and Bradberry-Greaves emotional intelligence questionnaire. Convenience sampling method was used and all nurses who had inclusion criteria were included. Suction performance checklist. The mean and SD scores of performance and emotional intelligence were 17.12+2.32 and 80.22+13.04 respectively. Pearson correlation did not show significant relationship between two variables (9=0.551, r=0.074). The Performance scores were related with work experience of nurses (p<0.05). The emotional intelligence and work history were not correlated (p>0.05). Conclusion: The results of current study showed no significant relationship between performance and emotional intelligence in a specific procedure of nurses. Since other studies showed positive relationship between emotional intelligence and performance, we recommend more studies with different questionnaires and more samples in their studies. Keywords: Emotional intelligence; Performance at Work; Suctioning